The Decline and Fall of Materia Medica and the Rise of Pharmacology and Therapeutics in Veterinary Medicine - Lees, Peter; Bäumer, Wolfgang; Toutain, Pierre-Louis (Frontiers in Veterinary Science, 2022)
Materia Medica is a Latin term, relating to the history of pharmacy. It describes the sources (vegetable, animal and mineral), nature, preparation and properties of substances or mixtures of substances, which were used as remedies for the treatment of diseases. Bourgelat authored the first veterinary Materia Medica book. This review describes the evolution and ultimate downfall of Materia Medica concepts and practices. Its survival for more than two millennia reflected the impact of religion and dogmas on therapy. The consignment of Materia Medica to history was signified by publication of the first modern book of veterinary pharmacology and therapeutics by Meyer Jones in 1953. Previously, the dominance of Materia Medica was linked to an hippiatry culture, which was shared with farriers and quacks. The Pasteurian and pharmacological revolutions of the second half of 19th century led to its gradual abandonment. This review explains why the existence of authentically active substances, such as opioid analgesics, cardiotonics and general anaesthetics either were not used for those actions or were badly prescribed, in part because of historical precedence and in part from lack of pathophysiological knowledge to justify rational use. The modern concept of dosage, in particular inter-species differences, was not understood. There were also major dogmas, supporting false indications, such as failure to recognize pain as a symptom to be treated, whereas inflammation was only a disease symptom involving excess of activity of the blood system, which had to be vigorously addressed by bleeding and purging.